Analysis the Mechanical Response of Tunnels Under the Action of Vertical Jacking in Shield Construction and Research on Reinforcement - Mingxun Hou; Chunshan Yang; Jiayi Yang; Yuefei Zeng; Zhigang Zhu (Buildings)
This research examines the effects of vertical jacking construction on the mechanical behavior of shield tunnels. Model tests simulating vertical jacking were performed utilizing a purpose-built apparatus to quantify the reaction forces generated by the diffusion block during the jacking operation. A systematic analysis was conducted on the mechanical responses of shield tunnel lining segments and their interconnecting joints. Utilizing Particle Flow Code (PFC) methodology, a deformation prediction model specifically tailored for vertical jacking conditions was formulated. Correlating simulation results with experimental measurements quantified the sensitivity of tunnel deformation to grouting reinforcement, enabling the identification of an optimal reinforcement zone. Key findings reveal that the jacking reaction force distribution exhibits pronounced nonlinearity: a substantial increase precedes failure, followed by rapid post-failure reduction and eventual stabilization in advanced jacking stages. Tunnel convergence deformation evolves through four distinct phases: significant growth, rapid attenuation, gradual diminution, and final stabilization. The primary zone of influence encompasses the opening ring and its two adjacent rings. Jacking induces longitudinal bending deformation, with maximum joint opening occurring at the opening ring. Abrupt longitudinal load fluctuations cause dislocation between the opening ring and neighboring rings. Internal segment stresses exhibit initial tensile and compressive increases followed by subsequent relaxation. Externally applied grouting reinforcement effectively attenuates jacking-induced tunnel deformation. An optimal reinforcement range was determined at the 60° position relative to the segment springline, substantially lowering resource consumption and construction risks compared to conventional reinforcement strategies. These outcomes furnish theoretical underpinnings and technical benchmarks for optimizing engineering design and facilitating the implementation of vertical jacking technology.